Pengaruh Live Streaming dan Affiliate Marketing Terhadap Keputusan Pembelian Online Melalui Media Sosial TikTok (Studi pada Mahasiswa Manajemen Pengguna TikTok) - Salsabila Nuarindah Ramli; M. Ikhwan Maulana Haeruddin; Muhammad Ilham Wardhana Haeruddin; Siti Hasbiah; Nurul Fadilah Aswar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the influence of live streaming and affiliate marketing on online purchasing decisions through social media Tiktok. Marketing has experienced significant developments in conventional methods such as print or television advertising that requires large costs, to social media the main tool for companies and consumers. This research is a quantitative study with a descriptive approach. The sample used was 102 students of the Management Study Program Faculty of Economics and Business, Makassar State University, Class of 2020-2022. Data collectionwas carried out using observation methods, literature studies, and surveys using questionnaires. The data analysis method uses multiple linear regression analysis using two statistical test methods, namely, partial test (t test) and simultaneous test (f test) using statistical product and service solutions (SPSS). Based on the research results, the results of the f-test hypotesis show that the calculated f value (155,779) > f table (3.088) with a significance level of (0,000) < (0,05) which means that the independent variables (Live Streaming X1 and Affiliate Marketing X2) simultaneously have a positive and significant influence on the Y variable (Purchase Decision). Meanwhile, the results of the t-test obtained the calculated t value of the live streaming variable (5.895) > t table (1.985) with a significance level of (0.000) < (0,05) which means that the X1 variable (Live Streaming) partially has a positive and significant influence on the Y variable obtained a calculated t value (4.870) > t table (1.984) with a significance level of (0,000) < (0,05) which means that the variable X2 (Affiliate Marketing) partially has a positive and significant influence on the variable Y (Purchase Decision).